UPAYA MENINGKATKAN KETERAMPILAN MENJELASKAN MATERI PADA MATA KULIAH MIKROTEACHING PROGRAM STUDI PENDIDIKAN BIOLOGI STKIP YPM BANGKO - Arista Ratih (Pendidikan Biologi STKIP YPM Bangko, 2021)
The practice of microteaching aims to improve students' abilities as prospective teachers in conducting teaching simulations in the classroom. This study aims to improve the skills of explaining material by students who carry out teaching simulations. This type of research is classroom action which consists of planning, implementing, observing and evaluating activities along with reflection. The research was conducted in 2 cycles, each cycle was carried out 2 times of teaching simulations. Data were analyzed qualitatively. The research subjects are students of biology education study program who teach microteaching courses. Based on the research that has been done, it was found that the increase in the ability to explain the material by students in cycle 1 was 71%, while in cycle 2 it was 81.5% with a percentage increase of 10.5%. From the data obtained, it can be concluded that this research can improve the ability of students to explain material skills in microteaching courses.